Changes in the temperature dependence of Ag/Ta2O5/Pt gapless-type atomic switches caused by desorption/adsorption of water molecules from/into the Ta2O5 matrix. (8th March 2021) - Mikami, Maiko; Tanahashi, Naoya; Tsuruoka, Tohru; Hasegawa, Tsuyoshi
Abstract: We measured, in vacuum, the temperature dependence of the Forming time in a Ag/Ta2 O5 /Pt gapless-type atomic switch, the results of which clearly suggest that the rate limiting process is the diffusion of Ag + cations in the Ta2 O5 layer. It is known that water molecules adsorbed in a Ta2 O5 matrix enhance the diffusion of Ag + cations, and this study further shows that desorbing water molecules by annealing at 623 K, which is known to be the desorption temperature of water molecules from Ta2 O5 matrixes, increases the diffusion barrier height from 0.38 to 1.1 eV. We found that annealing at much lower temperatures, e.g. 343 K, for a longer period of time can also desorb the said water molecules. Accordingly, we measured the Forming time in air, which resulted in a completely different temperature dependence. The rate limiting process of Forming changes from ionic diffusion to nucleation when the process is conducted in air.